2019
DOI: 10.1055/s-0039-3399529
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset, Long Illness Duration, Epilepsy Type, and Polypharmacy Have an Adverse Effect on Psychosocial Outcome in Children with Epilepsy

Abstract: Epilepsy is often associated with psychosocial comorbidity and this can be more disabling than the seizure activity. Still, these associated conditions are often underdiagnosed and therefore not sufficiently treated. We studied a large pediatric cohort of 371 patients with epilepsy to identify factors associated with negative outcome. We found that patients with early-onset epilepsy, epilepsy of known etiology, and polypharmacy were the most likely to display cognitive impairment. Behavioral problems were part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
10
1
1
Order By: Relevance
“…In contrast to our hypothesis, significant associations between illness duration and a child's EBPs were not found. Recently, an increase in EBPs was found only among CAWE with an illness duration of above 5 years [13]. As 80 % of our sample had an illness duration below 5-years, the lack of association between illness duration and a child's EBPs might be explained by the relatively short illness durations in our sample.…”
Section: Epilepsy and Behavioral And Emotional Problemscontrasting
confidence: 52%
See 3 more Smart Citations
“…In contrast to our hypothesis, significant associations between illness duration and a child's EBPs were not found. Recently, an increase in EBPs was found only among CAWE with an illness duration of above 5 years [13]. As 80 % of our sample had an illness duration below 5-years, the lack of association between illness duration and a child's EBPs might be explained by the relatively short illness durations in our sample.…”
Section: Epilepsy and Behavioral And Emotional Problemscontrasting
confidence: 52%
“…The findings from studies exploring relations between EBPs and a variety of child-related factors (e.g., age, gender) are inconsistent, with some studies reporting younger age and female gender to be associated with poorer psychosocial outcomes [7,[9][10][11] while others fail to provide such association [12]. Studies of the associations between epilepsy-related factors and a child's EBPs have indicated that polytherapy is one of the most significant risk factors for poor psychosocial outcome [13]. Early onset of seizures and extended illness duration were also associated with an increased risk for EBPs [13], with each additional year of epilepsy diagnosis, a child was reported to have a 1.35 times greater chance (95 % CI: 1.05-1.73) of having a psychiatric diagnosis [14].…”
Section: Emotional and Behavioral Problems Among Children With Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Catastrophic epilepsy in the sensitive developmental period of infancy, often associated with polypharmacy, can result in neurological deterioration and severely impaired quality of life [6,7]. Cognitive function decline has been associated with early-onset and long duration of epilepsy, calling for measures to terminate ongoing seizures [8,9].…”
Section: Introductionmentioning
confidence: 99%